Phenotypic Characters Analysis of Cross Melon (Cucumis melo L.) Tacapa Cultivar - Aristya, Ganies Riza; Onggo, Andika Tripramudya; Daryono, Budi Setiadi (2013)
Melon is one of horticulture commodities that are used as food. The world's need of melon is very high, but the melon is vulnerable to infection of powderry mildew. Tacapa was derived from crosses between PI 371795 and Action 434 with a test cross Action 434, which has resistant properties against powderry mildew. The study was conducted with the seeds come from the cross between PI 371795><Action 434 with a test cross of Action 434 in the greenhouse. Melon seedlings planted in KP4 field for 2 months, and fenotypic characters were analyzed. The analysis was conducted both quantitatively and qualitatively. Manual that was used for the analysis of the phenotype was International Plant Genetic Resources Institute (IPGRI) created by European Cooperative Programme for crop genetic resources Networks (ECPGR). Beside that, phenotype of Tacapa melon cultivars were also compared to the phenotype of four melons from the results of the previous crosses researches. Observation showed that derived character of Tacapa cultivar melons were stable and uniform. The results from phenotypic observation of Tacapa melon were: elliptical fruit shape, with a weight of 2.312 to 3.900 gram per fruit (fulfill the ‘A’ grade in Indonesia), sweet taste that has a level 1.4 from 5 scale (scale of 1 indicates very sweet taste), green-yellowish flesh, fruit skin has a tight net with a horizontal pattern, thick fruit flesh and the thickness of the skin is very thin just 0.24 millimeter, ripe fruit skin was green. Compared with the previous cultivar, Tacapa cultivar has some superiorities: more resistance to powdery mildew, longer durability (can be stored up to 21 days), bigger fruit size and higher level of sweetness. These characters show that cultivar Tacapa is one of the superior melon.